Discharge of thoracic patients on portable digital suction: Is it cost-effective?. (September 2015) - Southey, Dawn; Pullinger, Diane; Loggos, Spiros; Kumari, Nelam; Lengyel, Emma; Morgan, Ian; Yiu, Patrick; Nandi, Jayanta; Luckraz, Heyman
Objectives: A portable suction drainage device for patients undergoing thoracic surgical procedures was introduced into our service in January 2010. Patients who met strict discharge criteria were allowed to continue their treatment at home with the device. They were monitored in a designated follow-up clinic. Data were collected to identify the impact of this service in relation to the duration of follow-up required, bed-days saved, and potential cost/benefits. Methods: All patients who underwent a thoracic procedure from March 2012 to April 2014 and required suction postoperatively for air leak were included in the study. Patients were identified as suitable according to the discharge criteria. Data regarding patient demographics were collected prospectively on the thoracic database, and data on the drainage device were logged in a specific data sheet. Visits to the follow-up clinic were also recorded. Results: During the study period, 50 patients stayed a total 1125 days on the portable suction system. Twenty were discharged home, equating to 772 bed-days saved (GBP 270, 000 cost-saving). Clinic attendance totalled 162 visits (GBP 24, 300 cost reimbursement for attendance). Six (30%) patients were readmitted on 9 occasions due to device malfunction or inability to cope at home. Conclusion: Careful identification of patients suitable for discharge with a portable suction device achieved a significant cost-saving and freed hospital beds, thus allowing increased surgical activity. Patients were also able to be cared for within their home environment and maintain their quality of life.